Sistem Informasi Nilai Siswa Berbasis Web Pada SMP Negeri 26 Seluma - Inda Mareta Indriani; Khairil Khairil; Venny Novita Sari (Jurnal Media Infotama, 2025)
Student grading process is an important part of supporting the teaching and learning process in schools. However, at SMP Negeri 26 Seluma, the grading process is still done manually using Microsoft Word, which is prone to input errors, data duplication, and data loss. To address these issues, a web-based student grading information system was developed with the aim of improving efficiency, accuracy, and data security. The development method used is the Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The system was built using PHP programming language, MySQL database, and supported by frontend technologies HTML and CSS. The result of this research is an information system capable of effectively managing student grading data, enabling homeroom teachers to enter and process grades, and providing students with access to view their grades independently through a web portal. The implementation of this system is expected to improve the efficiency of school staff and academic information transparency at SMP Negeri 26 Seluma